ANALISIS PUSHOVER GEDUNG BLOK B PASAR SAWAHLUNTO - Nugroho, Fajar; Andrano, Reza; Maizir, Maizir (Jurnal Teknologi dan Vokasi, 2025)
Indonesia is a country with a high risk of earthquakes. Earthquake vibrations can cause ground shifts, which, in turn, affect building structures. To assess the level of risk for building damage, it is necessary to conduct a collapse scheme analysis and seismic performance evaluation of buildings. In this study, the author examined one of the earthquake-prone areas, Sawahlunto City, located in West Sumatra Province, Indonesia. The focus of the research is Block B of the Sawahlunto Market, a building that serves as a hub for community economic activities. The analysis employed is pushover analysis. The research methods include data collection, load calculations, 3D modeling, and static pushover analysis. Structural modeling was carried out using SAP2000 software. The structural performance level was evaluated based on SNI 1726-2019 and ATC-40 standards, and the mechanism of structural collapse was analyzed using plastic hinge formation. The analysis results show that the capacity curves in the X and Y directions have almost identical shapes, indicating that the structural stiffness along both axes is nearly the same. The performance points in the X and Y directions classify the building structure under the immediate occupancy category. This indicates that the building is highly capable of withstanding earthquakes with no significant damage.